Anteseden Information Adoption dan Pengaruhnya terhadap Purchase Intention Produk Emina pada Tiktok - Diva Septina Manik; Teguh Widodo (Universitas Batanghari Jambi, 2023)
The development of technology and the internet has made companies increasingly use platforms to execute their marketing strategies. One platform that is currently popularly used by the beauty industry is TikTok. Emina is one of the brands that is often seen on this platform. This study aims to analyze the antecedents of information adoption and its effect on purchase intention of Emina products. The method used is a quantitative method with the SEM model. The number of samples in this study were 221 respondents. The data analyzed is primary data collected using a questionnaire and processed using LISREL 8.8 software. There are five hypotheses in this study, the results showed that information adoption affects purchase intention.